Validation of a scale for the evaluation of the dimensions of short break tourist destination - Hamann, Antonieta (2023)
The present study’s aim is to design, construct and validate an instrument that allows for the measurement of the dimensions for short break tourist destination. The instrument was comprised of 29 items that were applied to 400 university students from diverse undergraduate in Lima, Peru through a convenience sampling. The analysis of the psychometric properties of the instruments and the construction of the perception scale of the short break destinations was carried out through application of Exploratory Factor Analysis and the Graduated Response Model from Item Response Theory. The results show a valid and reliable scale to measure a short break tourist destination. Moreover, show that evaluated individuals tend to positively rate the attributes of the short break destinations they have visited and that tourist perceive the measured attributes as expected characteristic when they visit that destination. The scale proposed fills the gap to measure the dimensions that the visitor would like to find in a short break destination, to group the perception of the attributes that tourists seek in a holistic way. In so doing, the tourist will visit a place that is capable of meeting their expectations and that allows them to establish a link with the destination.